(untitled) (Journal of University of Babylon for Engineering Sciences, 2019)
The aims of this investigation is to survey influence of ND:YAG Laser surface treatment of dry sliding wear features of EN 24 steel, which is medium carbon low alloy steel. Many parts of automotive, railways, marine and electric power generators are made from this alloy with distinctive properties as high strength and good wear resistance. According to ASTM G99 standards, length and diameter of the samples were (2 and 1) cm prepared by lathe machining. The prepared specimens were heat treated by using pulse ND: YAG Laser of 1064 nm wavelength and 6 Hz frequency with different energies as 500, 750 and 1000 mJ for 10 pulses. Whilst, wear inspect with dry slipping was carried out in pin–on–disc mechanism through changing loads and times from 5, to 25 N and 5 to 30 min in 5 intervals respectively. In addition, roughness and microhardness examinations were performed for the samples as received and after wear test. Photomicrographs were taken for the samples before, after surface Laser treatment, before, and after wear test. Results obtained increasing in hardness with improving in wear resistance. Surface roughness of treated specimens with 1000 mJ was more than with 500 and 750 mJ energies.